La parálisis cognitiva sumatoria de determinantes socioculturales - Pardo Abril, Neyla Graciela; Hernández Vargas, Edwar Eugenio (Enunciación, 2006)
Cognitive paralysis ia a theoretical effort made in order to establish frameworks to understand the relationships between representation, discourse and cognition. ln this case, the emphasis is placed on the group of discursive processes that favour limited comprehension ofsocio-cultural phenomena, due to the impact of interaction models. Those interaction models are srestructured as representation. Here, the espectacularization, naturalization and hiding as discoursive processes that, established from emotional production, durability and meanin gaps, burst in the action of knowing.